2011
DOI: 10.1016/j.healthpol.2010.06.025
|View full text |Cite
|
Sign up to set email alerts
|

The opinion of adolescents and adults on Dutch restrictive and educational alcohol policy measures

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. a b s t r a c tObjectives: The main objective of this study is to explore the opinion of 16-22-year olds on alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 13 publications
(23 reference statements)
2
11
1
Order By: Relevance
“…Policies directed toward curbing excessive consumption and irresponsible service have greater public support than do policies that affect all drinkers [12][13][14]. It is perhaps not surprising that support for strategies that restrict availability tends to be lower among people who drink more [10,[13][14][15][16][17][18]. Greater support for alcohol control strategies is expressed by women and older people [9,10,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Policies directed toward curbing excessive consumption and irresponsible service have greater public support than do policies that affect all drinkers [12][13][14]. It is perhaps not surprising that support for strategies that restrict availability tends to be lower among people who drink more [10,[13][14][15][16][17][18]. Greater support for alcohol control strategies is expressed by women and older people [9,10,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Whether adolescents' support of e‐cigarette regulation is equally high in legislatures with weaker tobacco control laws remains to be explored. Thirdly, in accordance with previous studies which have shown that the views on regulation of consumers of addictive substances differ by respondents' characteristics 12, 13, 23, we conducted a basic analysis of differences in opinions with regard to smoking status and e‐cigarette use. More detailed analyses accounting for correlations between other socio‐economic variables and adolescent opinions on e‐cigarette regulation remain outstanding.…”
Section: Discussionmentioning
confidence: 75%
“…Public opinion on, and acceptance of, existing and future public policies matter because levels of acceptability and support can critically affect policy effectiveness 12. Reviewing the opinion of target populations increases the chances of success of public health policy 13, and high levels of public support can enhance compliance 14. US research suggests that political decision makers are disposed to act in accordance with public opinion 15, possibly with a view to increasing their chances of re‐election 12.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations